Laicity in Jujuy in light of the constitutional reforms, the ecclesiastical reality and the political contexts (1893-1955) (Quinto Sol, 2022)
The article offers an approach to the issue of laicity in Jujuy, placing the focus in the texts of the five constitutional letters that the province sanctioned between the end of the 19th century and the middle of the 20th, and in the respective constitutional conventions. In addition to referring to the political contexts in which these reforms were inscribed, the central guidelines of the ecclesiastical reality of the northern province are traced throughout the decades considered. The focus is put on some specific events and moments in search for keys to understand the persistence of a peculiar feature of the local political scene, which is the scant gravitation that the Church and its organizations had in it, in strong contrast with the vivid manifestations of popular faith throughout the provincial geography. The rhythms, scope and periodization of the secularization process in Argentina are topics still open to debate and there are several calls to allow for the specificities of scenarios and contexts in each local space, providing the historical analysis with a more solid empirical basis. The lines that follow intend to make a contribution in this sense
Keywords: laicity; provincial constitutions; ecclesiastical reality